The Modern Portrait of The American Family in Sam Shepard's True West (Journal of Imam Al-Kadhim College, 2023)
Sam Shepard (1943-2017) was born to Sam Rogers the sixth and Jane Elaine Schook Rogers on Nov. 1943 in Fort Sheridan, Illinois. To keep the family tradition, he was nicknamed Steve to distinguish him from his father who was a military man. The family was moving from a place to another before staying in a farm in California where they raised sheep and grew avocados. At the age of eleven and while Shepard was studying at school, he received a copy of Samuel Beckett's Waiting For Godot from one of his friends which was a new experience for him. In 1963, Shepard moved to New York where his talent of writing developed. He found himself in the middle of a rapidly transforming social and cultural world. At that time, he changed his name from Steve Rogers to Sam Shepard to break his heredity of the name and to distance himself from the ties of the family. He was awarded the Pulitzer Prize in 1978 due to his masterpiece Buried Child.